Efektywność projektów usprawniających procesy logistyczne mierzona za pomocą wskaźnika głównego i wskaźnika pomocniczego - Kawa, Arkadiusz; Śliwka, Radosław; Solecki, Bartosz (The Efficiency of Projects Improving Logistic Processes Measured by the Main Indicator and the Supplementary Indicator, 2008)
In this paper the goals and range of logistic projects are described and indicators which serve to evaluate their efficiency are presented. The DMAIC method is introduced as the basic tool in carrying out projects based on Six Sigma, too. In order to better illustrate the various possibilities of doing projects aiming at improving logistic processes in global companies, the authors compare the DMAIC method with a similar corporate MEDIC method. The goal of this paper is to collect the theoretical basis for the choice of the rights indicators intended for solving logistic problems and the presentation of practical advice and experience resulting from using those indicators during logistic projects.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 28-50